PENGARUH PROMOSI PERSONAL SELLING DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Purnama, Zulfa Aulia (Jurnal Pijar, 2024)
Purchasing decisions can be influenced by several factors, for example, personal selling and product quality. The purpose of this study is that researchers want to know how much influence personal selling promotions and product quality have on consumer purchasing decisions at CV. Queenra Mandiri. The test in this study was carried out with the help of SPSS 29.0.2.0, with the analysis methods used in this study, namely the validation test, reliability test, multiple regression test, normality test, multicollinearity test, heteroscedasticity test, glejser test, hypothesis test (t test and F test), and the coefficient of determiination used in this study. The results showed that Personal Selling Promotion obtained results with T < 0.001 while Product Quality was 0.001 which means that the hypothesis is accepted because both variables have a positive and significant effect on consumer purchasing decisions.. And F count 94.941> F table 3.15, the results show that the three variables together have a significant effect on consumer purchasing decisions.